CAMEL Ratio on Profitability Banking performance: Case Studies of Banks in Indonesia - Wastam Wahyu Hidayat (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
A The purpose of the study was to determine whether there was an effect of the CAMEL variable (CAR, AEPA, NIM, BOPO, and LDR) on the profitability variable (ROA), in banking companies in Indonesia for the 2014-2018 period. The population and sample in this study are banking companies in Indonesia. The data collection technique is sample data from the Indonesia Stock Exchange. In this study data analysis using SPSS version 23. The indicators used in the CAMEL analysis are CAR (Capital Adequacy Ratio), AEPA (Allowance for Earning Assets), NIM (Net Interest Margin), ROA (Return on Assets), LDR (Loan to Deposit Ratio). Based on the results of the study, CAR does not affect profitability (ROA), while the variables: AEPA, NIM, BOPO, and LDR affect profitability. The purpose of this study is to provide input on banking conditions so that banks can improve weaknesses so that banks can get the expected benefits.